ACHIEVEMENT OF THE BUDDHA’S KEY DISCOURSES - Srinonyang, Pradit (วารสารศรีล้านช้างปริทรรศน์, 2019)
The objectives of the academic article were (1) to study the achievement of the learners from the Buddha’s teaching of key discourses, and (2) to study the Buddha’s teaching techniques. Based on the first-resource and second-resource documents -- Thai-language Tripitaka, commentaries, Buddhism dictionaries, etc., the case study was focused on such key discourses as Dhammacakkappavatana Sutta, Anattalakkhaṇa Sutta, Ādittapariyāya Sutta, Anupubbikathā and Ariyasacca, Vedanāpariggaha Sutta and Abhidhamma since these discourses were involved with the Buddha’s important events and disciples. Besides, the success of the Buddha’s teaching was depended upon the appropriate combination of the basic course in accordance with the higher course, which assisted his learners in realizing what he taught.